Bonding method of polyurethane adhesive for organic glass and tensile shear strength sample
By grinding and cleaning in the bonding process of polyurethane adhesive for plexiglass, and combining the use of base glue and polyurethane adhesive, the problem of difficult to control the bonding performance is solved. At the same time, a tensile shear strength sample of structural adhesive bonded steel sheet bottom plate and compensation pad is designed to ensure that the center line of the sample coincides with the force line, and improve the accuracy of the test.
Patent Information
- Application Number
- CN202411434403.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-02-25
AI Technical Summary
The bonding process of existing polyurethane adhesives for plexiglass has failed to effectively control the bonding performance, and the traditional pull-shearing sample design does not overlap with the center line, which affects the accuracy of the test.
A method of bonding for polyurethane adhesive for plexiglass is provided, including grinding and cleaning in the bonding area, bonding using a base glue and a polyurethane adhesive, and controlling temperature and humidity during curing. At the same time, a tensile shear strength sample is designed to bond the steel sheet bottom plate and the compensation pad through structural adhesive to ensure that the center line of the sample and the force line overlap.
It improves the controllability and reliability of adhesive properties, ensures that the test is subjected to uniform stress during the tensile process, improves the accuracy of the test, and avoids the problem of product debonding.
Smart Images

Figure CN119505720A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material preparation and strength testing, and in particular relates to a bonding method of polyurethane adhesive for organic glass and a tensile shear strength test specimen. Background Art
[0002] Polyurethane adhesives are widely used in the bonding of transparent parts in the fields of construction, automobiles, high-speed rail, aviation, etc. due to their high strength, strong tear resistance, excellent softness and wear resistance. Unlike the application scenarios of bonding transparent parts to metal materials in the fields of construction, automobiles, high-speed rail, etc., the bonding of transparent parts in the aviation field is mainly based on plexiglass and composite materials, and involves some occasions of bonding plexiglass to plexiglass. Any material application has its limitations. For applications in the aviation field, the bonding performance of polyurethane adhesives for plexiglass is often difficult to control. In addition to the performance of the adhesive itself, it has a lot to do with the bonding process. Different process processes and process parameters will have a great impact on the bonding properties such as bonding strength, failure form, and environmental resistance. In addition, when evaluating the bonding performance of the adhesive, it is also necessary to prepare a tensile shear strength specimen. The traditional test method is: use an adhesive to bond and cure two parallel rectangular sample sheets to form a lap structure, and then the two ends are clamped and fixed by the chuck of a universal material testing machine, such as Figure 1 As shown, after applying tension to both ends, the maximum tensile shear force at which the bonding part of the sample is destroyed is measured.
[0003] Practical applications and tests have shown that the current bonding process and shear test specimens have the following technical problems: 1) The bonding process does not standardize the operating details, resulting in the bonding structure being easy to debond during use; 2) Polyurethane adhesives are very sensitive to environmental factors, especially temperature and humidity. The existing bonding process does not determine the process window, and the reliability of the bonding structure is difficult to guarantee; 3) The center line of the traditional shear test specimen does not coincide with the tensile force line of the testing machine. The specimen will be twisted and deformed under the action of eccentric force, affecting the test accuracy; 4) The testing machine directly clamps the plexiglass specimen. If the tension is too large, the specimen will be destroyed before the adhesive layer is destroyed, resulting in the inability to measure the maximum tensile shear force as required.
[0004] Therefore, it is necessary to propose a polyurethane adhesive bonding method for organic glass and a tensile shear strength test specimen. Summary of the invention
[0005] In view of the above technical problems, the present invention provides a bonding method of polyurethane adhesive for organic glass and a tensile shear strength test specimen, and the technical scheme is as follows:
[0006] In a first aspect, a method for bonding a polyurethane adhesive for organic glass is provided, which is used for bonding a first object and a second object, wherein the first object is organic glass and the second object is a composite material or organic glass, and the method comprises the following steps:
[0007] Step 1. Divide the bonding area on the first object and the second object according to the drawing requirements, and affix a pressure-sensitive tape on the non-bonding area adjacent to the bonding area for protection;
[0008] Step 2. Use sandpaper of preset specifications to grind the bonding area of the first object and the second object until the surface loses its gloss;
[0009] Step 3. Remove the pressure-sensitive tape, use a dust-free cloth dipped in anhydrous ethanol to clean the bonding area and let it air dry;
[0010] Step 4. Stick the pressure-sensitive tape again to the non-adhesive area adjacent to the adhesive area;
[0011] Step 5. Use medical gauze to dip the primer, apply it evenly on the bonding area and let it dry;
[0012] Step 6. Use a glue gun to inject polyurethane adhesive onto the surface of the bonding area;
[0013] Step 7. Assemble the first object and the second object together to obtain a bonded integral part, and press the first object until polyurethane adhesive overflows from the edge of the bonding area;
[0014] Step 8. Static curing of the bonded integral part is performed under the environmental conditions of a temperature of 23°C ± 2°C and a relative humidity of 50% ± 5%. After curing for a certain period of time, the residual glue is cleaned or the workpiece is moved, and the curing is continued for a certain period of time, and the workpiece is processed or transferred to the next process; when the bonded integral part is statically cured under the environmental conditions of a temperature not lower than 15°C and a relative humidity of 15% to 75%, a tensile shear strength test is performed using a plexiglass tensile shear furnace sample. When the tensile shear strength of the sample is not lower than τ1, the residual glue of the bonded integral part is cleaned or the workpiece is moved. Then, when the tensile shear strength of the sample is not lower than τ2, the bonded integral part is processed or transferred to the next process; wherein τ1 is 2.5MPa and τ2 is 3.5MPa;
[0015] Step 9. Detect the bonding surface of the first object, measure the defect size, count the defect area, and determine whether the bonding requirements are met.
[0016] Optionally, in step 2, the sandpaper used to polish the organic glass bonding area has a specification of 300-1000 mesh, and the sandpaper used to polish the composite material bonding area has a specification of 100-1000 mesh. The effect is that the roughness of the polishing is higher, and the bonding strength of the bonding is improved.
[0017] Optionally, in step 3, the air-drying time is 10 to 20 minutes, so as to allow the anhydrous ethanol to fully evaporate and avoid affecting the bonding effect.
[0018] Optionally, in step 5, the air-drying time is 10 minutes to 300 minutes. The effect is to ensure that the base glue can be fully cured and improve the bonding effect of the polyurethane adhesive.
[0019] Optionally, in step 8, after curing for 24 hours under the environmental conditions of temperature 23°C ± 2°C and relative humidity 50% ± 5%, the remaining glue is cleaned or the workpiece is moved, and the curing is continued for 72 hours before processing or transfer to the next process.
[0020] Optionally, in step 9, the bonding requirement is that the size of a single bonding defect shall not exceed 60 mm. 2 , the total defect area does not exceed 5% of the total bonding area.
[0021] In a second aspect, a tensile shear strength specimen is provided, comprising a first specimen and a second specimen, wherein the first specimen is organic glass, and the second specimen is a composite material or organic glass.
[0022] The two samples are both rectangular sheets as the shape, and are connected by a polyurethane adhesive coated on the rectangular overlapping area, and the polyurethane adhesive is formed on the overlapping area by the bonding method of the polyurethane adhesive for organic glass as described in any one of claims 1 to 6;
[0023] The back of the overlapped surface of each specimen is bonded with a steel plate bottom plate of the same size as the specimen by means of structural adhesive, and a compensation pad is bonded to the clamping end of each specimen by means of the same structural adhesive, and one end of the compensation pad is directly clamped in the chuck of the universal material testing machine;
[0024] The first specimen and the second specimen have the same length and width. The thickness of specimen 1 is T1, the thickness of the second specimen is T2, the thickness of the steel sheet bottom plate on one side of the first specimen is e1, and the thickness of the compensation pad is f1, the thickness of the steel sheet bottom plate on one side of the second specimen is e2, and the thickness of the compensation pad is f2, the thickness of the structural adhesive between the specimen and the steel sheet bottom plate, and the thickness of the structural adhesive between the specimen and the compensation pad is t, and the thickness of the polyurethane adhesive layer for organic glass at the overlap of the first specimen and the second specimen is T;
[0025] The thickness of the rectangular thin sheet in the overlapping area on the first specimen is T1+e1+t, and the thickness of the rectangular thin sheet in the overlapping area on the second specimen is T2+e2+t, and T1+e1+t=T2+e2+t, f1=T2+e2+T, f2=T1+e1+T, to ensure that the center line of the specimen coincides with the tensile force line of the testing machine, avoid distortion of the specimen under the action of eccentric force, and improve the accuracy of the test.
[0026] Optionally, the organic glass is biaxially stretched organic glass, cast organic glass or injection molded organic glass, and the composite material is an epoxy resin-based carbon fiber composite material.
[0027] Optionally, the polyurethane adhesive for organic glass is a single-component polyurethane adhesive; the structural adhesive is a two-component polyurethane adhesive, an acrylate adhesive or an epoxy resin-based adhesive, and the tensile elastic modulus is similar to the tensile elastic modulus of the sample.
[0028] Optionally, the curing conditions of the structural adhesive are curing at room temperature for seven days, or heating curing at 60° C. for eight hours.
[0029] The beneficial effects of the present invention are at least:
[0030] 1. The bonding method of the present invention has low cost and strong adaptability, and can be used for bonding organic glass and composite materials, organic glass and organic glass using polyurethane adhesive;
[0031] 2. The key process of this bonding method is clear, the parameters are clear, and the feasibility is strong. Through grinding and cleaning, the influence of manufacturing and environmental factors on the bonding surface of the substrate can be eliminated; by determining the coating method and air-drying time, the activation effect of the primer on the bonding surface of the substrate can be guaranteed; by controlling the curing temperature, curing humidity and curing time, the curing rate and bonding performance can be guaranteed, and the product debonding can be effectively avoided;
[0032] 3. This bonding method specifies a defect detection method, which is simple to operate and easy to identify;
[0033] 4. The tensile shear strength specimen of the present invention can ensure that the center line of the specimen coincides with the force line, ensuring that the specimen is subjected to uniform force during the tensile process and reaches a force state close to pure shear;
[0034] 5. The sample of the present invention can ensure that the sample will not be damaged before the adhesive in the test area is damaged;
[0035] 6. The specimen of the present invention has a simple structure, is easy to process, and has strong design adaptability. It can be used for tensile shear strength testing of specimens of different thicknesses by simply matching and adjusting the thickness parameters. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 It is a tensile effect diagram of the tensile shear strength specimen of the existing polyurethane adhesive for organic glass after being connected to the chuck of the universal material testing machine;
[0037] Figure 2 A three-dimensional view of a tensile shear strength specimen of a polyurethane adhesive for organic glass provided in an embodiment of the present application;
[0038] Figure 3A front view of a tensile shear strength test specimen of a polyurethane adhesive for organic glass provided in an embodiment of the present application;
[0039] Figure 4 A side view of a tensile shear strength specimen of a polyurethane adhesive for organic glass provided in an embodiment of the present application;
[0040] Figure 5 A flow chart of a bonding method of polyurethane adhesive for organic glass provided in an embodiment of the present application;
[0041] Figure 6 This is a diagram of the tensile effect of the tensile shear strength specimen of the polyurethane adhesive for organic glass provided in the embodiment of the present application after being connected to the chuck of a universal material testing machine. DETAILED DESCRIPTION
[0042] The present invention is further described in detail below through specific implementation modes and drawings.
[0043] One embodiment of the present invention provides a method for bonding organic glass with a polyurethane adhesive, see Figure 5 , used for gluing a first object to a second object, the first object is organic glass, and the second object is a composite material or organic glass, the bonding method comprises the following steps:
[0044] Step 1. Divide the bonding area on the first object and the second object according to the drawing requirements, and affix a pressure-sensitive tape on the non-bonding area adjacent to the bonding area for protection;
[0045] Step 2. Use sandpaper of preset specifications to grind the bonding area of the first object and the second object until the surface loses its gloss;
[0046] Step 3. Remove the protective tape, use a dust-free cloth dipped in anhydrous ethanol to clean the bonding area and let it air dry;
[0047] Step 4. Stick the pressure-sensitive tape again to the non-adhesive area adjacent to the adhesive area;
[0048] Step 5. Use medical gauze to dip the primer, apply it evenly on the bonding area and let it dry;
[0049] Step 6. Use a glue gun to inject polyurethane adhesive onto the surface of the bonding area;
[0050] Step 7. Assemble the first object and the second object together to obtain a bonded integral part, and press the first object until polyurethane adhesive overflows from the edge of the bonding area;
[0051] Step 8. Perform static curing of the bonded integral part under environmental conditions of a temperature of 23°C ± 2°C and a relative humidity of 50% ± 5%. After curing for a certain period of time, clean up the remaining glue or move the workpiece, continue curing for a certain period of time, and then process or transfer to the next process. When the bonded integral part is statically cured under environmental conditions of a temperature not lower than 15°C and a relative humidity of 15% to 75%, use a plexiglass tensile shear furnace sample to perform a tensile shear strength test. When the tensile shear strength of the sample is not lower than τ1, clean up the remaining glue or move the workpiece. Then, when the tensile shear strength of the sample is not lower than τ2, process the bonded integral part or transfer to the next process. Among them, τ1 is 2.5MPa and τ2 is 3.5MPa.
[0052] Step 9. Detect the bonding surface of the first object, measure the defect size, count the defect area, and determine whether the bonding requirements are met.
[0053] An embodiment of the present invention further provides a tensile shear strength test specimen, comprising a test specimen 1 (a first test specimen) and a test specimen 2 (a second test specimen), wherein the test specimen 1 is organic glass, and the test specimen 2 is a composite material or organic glass, see Figure 2 , Figure 3 and Figure 4 The two specimens are both rectangular sheets as the shape, and are connected by polyurethane adhesive coated on the rectangular overlap area, and the polyurethane adhesive is formed on the overlap area by the bonding method of polyurethane adhesive for organic glass provided by the embodiment of the present invention. The back of the overlap surface of each specimen is bonded with a steel sheet bottom plate of the same size as the specimen by structural adhesive, and a compensation pad is bonded to the clamping end of each specimen by the same structural adhesive, and one end of the compensation pad is directly clamped in the chuck of the universal material testing machine.
[0054] Sample 1 and Sample 2 have the same length and width. The thickness of Sample 1 is T1, and the thickness of Sample 2 is T2. The thickness of the steel sheet bottom plate 4 on one side of Sample 1 is e1, and the thickness of the compensation pad 5 is f1. The thickness of the steel sheet bottom plate 7 on one side of Sample 2 is e2, and the thickness of the compensation pad 8 is f2. The thickness of the adhesive layer 6 of the structural adhesive between the sample and the steel sheet bottom plate and the structural adhesive between the sample and the compensation pad is t. The thickness of the polyurethane adhesive layer 3 for organic glass at the overlap of Sample 1 and Sample 2 is T.
[0055] The thickness of the rectangular thin sheet in the overlapping area on sample 1 is T1+e1+t, and the thickness of the rectangular thin sheet in the overlapping area on sample 2 is T2+e2+t, and T1+e1+t=T2+e2+t, f1=T2+e2+T, f2=T1+e1+T, to ensure that the center line of the sample coincides with the tensile force line of the testing machine, avoid distortion of the sample under the action of eccentric force, and improve the accuracy of the test.
[0056] Preferably, in step 2 of the bonding method, the sandpaper used to polish the bonding area of the organic glass has a specification of 300-1000 mesh, and the sandpaper used to polish the bonding area of the composite material has a specification of 100-1000 mesh;
[0057] Preferably, in step 3 of the bonding method, the air-drying time is 10 min to 20 min;
[0058] Preferably, in step 5 of the bonding method, the air-drying time is 10 min to 300 min;
[0059] Preferably, in step 8 of the bonding method, after curing for 1 day, the residual glue can be cleaned or the workpiece can be moved, and after curing for 3 days, the workpiece can be processed or transferred to the next process;
[0060] Preferably, in step 8 of the bonding method, after curing for 24 hours under the environmental conditions of a temperature of 23°C ± 2°C and a relative humidity of 50% ± 5%, the residual glue is cleaned or the workpiece is moved, and after continuing to cure for 72 hours, processing or transfer to the next process is performed;
[0061] Preferably, in step 9 of the bonding method, the bonding requirement is that the size of a single bonding defect shall not exceed 60 mm2, and the total area of the defects shall not exceed 5% of the total bonding area;
[0062] Preferably, the organic glass used in the tensile shear strength specimen is biaxially stretched organic glass, cast organic glass or injection molded organic glass; the composite material is an epoxy resin-based carbon fiber composite material;
[0063] Preferably, in the tensile shear strength test specimen, the polyurethane adhesive for organic glass used is a single-component polyurethane adhesive; the structural adhesive is a two-component polyurethane adhesive, an acrylate adhesive or an epoxy resin-based adhesive, and the tensile elastic modulus is similar to the tensile elastic modulus of the test specimen;
[0064] Preferably, for the tensile shear strength test specimen, the curing condition of the structural adhesive is curing at room temperature for seven days, or heating curing at 60° C. for eight hours.
[0065] An embodiment of the present invention provides a bonding method of polyurethane adhesive for organic glass, and also provides a tensile shear strength specimen. The following embodiment describes the application of the proposed bonding method to the preparation process of the tensile shear strength specimen.
[0066] Embodiment 1:
[0067] Cast organic glass was used for bonding the first object and sample 1; epoxy resin-based carbon fiber composite laminate was used for bonding the second object and sample 2; Sikaflex265 was used as adhesive and SikaPrimer209D was used as primer.
[0068] In this embodiment, the size of the bonding object and the sample are consistent. Figure 2 to Figure 4 The length of the sample is L = 100 mm, the width is W = 25 mm, the length of the bonding area is P = 12.5 mm, the thickness of the polyurethane adhesive is T = 1 mm, the thickness of sample 1 is T1 = 3 mm, the thickness of sample 2 is T2 = 1.8 mm, the thickness of the steel sheet bottom plate 4 on one side of sample 1 is e1 = 1 mm, the thickness of the compensation pad 5 is f1 = 5 mm, the thickness of the steel sheet bottom plate 7 on one side of sample 2 is e2 = 2.2 mm, the thickness of the compensation pad 8 is f2 = 5 mm, and the thickness of the structural adhesive layer 6 of the steel sheet bottom plate and the compensation pad is t = 0.5 mm.
[0069] The bonding is carried out under the environmental conditions of temperature 23℃±2℃ and relative humidity 50%±5%, including the following steps:
[0070] S1. Press Figure 3 It is required to divide the bonding area on the first object and the second object, and to stick a pressure-sensitive tape on the non-bonding area adjacent to the bonding area for protection.
[0071] S2. Use 500-grit sandpaper to sand the first object bonding area and use 300-grit sandpaper to sand the second object bonding area until the surface loses its gloss.
[0072] S3. Remove the protective tape, use a dust-free cloth dipped in anhydrous ethanol to clean the bonding area and let it air dry for 15 minutes.
[0073] S4. Use pressure-sensitive tape again to protect the non-bonding area adjacent to the bonding area.
[0074] S5. Dip the primer into medical gauze, apply it evenly on the bonding area and let it dry for 20 minutes.
[0075] S6. Use a glue gun to inject the polyurethane adhesive onto the surface of the bonding area. If necessary, use a scraper to evenly apply the adhesive.
[0076] S7. Assemble the first object and the second object together to obtain a bonded integral part, and press the first object until polyurethane adhesive overflows from the edge of the bonding area.
[0077] S8. Static curing at 23°C and 50% relative humidity. After 24 hours of curing, clean up the remaining glue. After 72 hours of curing, proceed to the next step.
[0078] S9. Check the bonding surface of the first object and measure the defect size. The size of a single bonding defect shall not exceed 60 mm. 2 , the total defect area does not exceed 5% of the total bonding area.
[0079] S10. After the defect inspection meets the requirements, the bonding is completed.
[0080] If you need to further judge the bonding effect, continue to prepare and test the tensile shear strength specimens in the following manner:
[0081] Use SY-51 structural adhesive to bond steel plate bottom plates of specified sizes to the back of the overlapped surfaces of specimens 1 and 2, and bond a compensation pad to the clamping end of each specimen. After bonding, it needs to be cured at room temperature for seven days.
[0082] After curing is completed, the two ends of the test piece are fixedly clamped on the universal material testing machine with a test chuck, and the testing machine is started to apply force to the two ends for stretching at a stretching speed of 6 mm / min until the bonding part is damaged.
[0083] The tensile shear strength can be calculated by the following formula: b When it is not less than 3.5MPa, it can be determined that the tensile shear strength test has passed.
[0084]
[0085] Where P is the length of the bonding area, W is the width of the bonding area, F is the maximum tensile shear force F when the bonding part is damaged, τ b is the tensile shear strength.
[0086] Embodiment 2:
[0087] Biaxially stretched organic glass was used to bond the first object and sample 1; injection molded organic glass was used to bond the second object and sample 2; Sikaflex265 was used as adhesive and SikaPrimer209D was used as primer.
[0088] In this embodiment, the size of the bonding object and the sample are consistent. Figure 2 to Figure 4 The length of the sample is L = 100 mm, the width is W = 25 mm, the length of the bonding area is P = 12.5 mm, the thickness of the polyurethane adhesive is T = 1 mm, the thickness of sample 1 is T1 = 3 mm, the thickness of sample 2 is T2 = 4 mm, the thickness of the steel sheet bottom plate 4 on one side of sample 1 is e1 = 2 mm, the thickness of the compensation pad 5 is f1 = 6 mm, the thickness of the steel sheet bottom plate 7 on one side of sample 2 is e2 = 1 mm, the thickness of the compensation pad 8 is f2 = 6 mm, and the thickness of the structural adhesive layer 6 of the steel sheet bottom plate and the compensation pad is t = 0.5 mm.
[0089] The bonding is carried out under the environmental conditions of temperature 20℃ and relative humidity 60%. The furnace samples need to be pretreated as follows:
[0090] Use SY-51 structural adhesive to bond steel plate bottom plates of specified sizes to the back of the overlapped surfaces of specimens 1 and 2, and bond a compensation pad to the clamping end of each specimen. After bonding, it needs to be cured at room temperature for seven days.
[0091] After the pretreatment of the furnace parts is completed, the bonding is carried out according to the following steps:
[0092] S1. Press Figure 3 It is required to divide the bonding area on the first object and the second object, and to stick a pressure-sensitive tape on the non-bonding area adjacent to the bonding area for protection.
[0093] S2. Use 500-grit sandpaper to sand the bonding area between the first object and the second object until the surface loses its gloss.
[0094] S3. Remove the protective tape, use a dust-free cloth dipped in anhydrous ethanol to clean the bonding area and let it air dry for 15 minutes.
[0095] S4. Use pressure-sensitive tape again to protect the non-bonding area adjacent to the bonding area.
[0096] S5. Dip the primer into medical gauze, apply it evenly on the bonding area and let it dry for 20 minutes.
[0097] S6. Use a glue gun to inject the polyurethane adhesive onto the surface of the bonding area. If necessary, use a scraper to evenly apply the adhesive.
[0098] S7. Assemble the first object and the second object together to obtain a bonded integral part, and press the first object until polyurethane adhesive overflows from the edge of the bonding area.
[0099] S8. Static curing at 20°C and 60% relative humidity. When the tensile shear strength of the sample is not less than 2.5MPa, clean the remaining glue. When the tensile shear strength of the sample is not less than 3.5MPa, proceed to the next step.
[0100] S9. Check the bonding surface of the first object and measure the defect size. The size of a single bonding defect shall not exceed 60 mm. 2 , the total defect area does not exceed 5% of the total bonding area.
[0101] S10. After the defect inspection meets the requirements, the bonding is completed.
[0102] In step S8, the method for testing the tensile shear strength of the furnace sample is as follows:
[0103] Use a test chuck to fix the two ends of the furnace sample on the universal material testing machine, start the testing machine to apply force to the two ends for stretching, and the stretching speed is 6mm / min until the bonding part is damaged.
[0104] The tensile shear strength can be calculated by the following formula: b When it is not less than 3.5MPa, it can be determined that the tensile shear strength test has passed.
[0105]
[0106] Where P is the length of the bonding area, W is the width of the bonding area, F is the maximum tensile shear force F when the bonding part is damaged, τ b is the tensile shear strength.
[0107] See also Figure 6 , which is a diagram of the tensile effect after the tensile shear strength specimen of the polyurethane adhesive for organic glass provided in the embodiment of the present application is connected to the chuck of a universal material testing machine.
[0108] The polyurethane adhesive bonding method for organic glass provided by the present invention is also suitable for bonding large-size double-curvature organic glass and composite materials.
[0109] The tensile shear strength test specimen provided by the present invention can be used under non-standard environmental conditions with a temperature not lower than 15°C and a relative humidity of 15% to 75%. Of course, under standard environmental conditions with a temperature of 23°C ± 2°C and a relative humidity of 50% ± 5%, if the bonding effect needs to be accurately determined, a tensile shear strength test is required. Any other scenarios requiring a tensile shear strength test can also use the tensile shear strength test specimen provided by the present invention.
[0110] The above only expresses the implementation mode of the present invention, and its description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. In addition, the parts not detailed in the present invention are all conventional technologies.
Claims
1. A method for bonding organic glass with a polyurethane adhesive, characterized in that: Used for gluing a first object to a second object, the first object is organic glass, and the second object is a composite material or organic glass, the method comprises the following steps: Step 1. Divide the bonding area on the first object and the second object according to the drawing requirements, and affix a pressure-sensitive tape on the non-bonding area adjacent to the bonding area for protection; Step 2. Use sandpaper of preset specifications to grind the bonding area of the first object and the second object until the surface loses its gloss; Step 3. Remove the pressure-sensitive tape, use a dust-free cloth dipped in anhydrous ethanol to clean the bonding area and let it air dry; Step 4. Stick the pressure-sensitive tape again to the non-adhesive area adjacent to the adhesive area; Step 5. Use medical gauze to dip the primer, apply it evenly on the bonding area and let it dry; Step 6. Use a glue gun to inject polyurethane adhesive onto the surface of the bonding area; Step 7. Assemble the first object and the second object together to obtain a bonded integral part, and press the first object until polyurethane adhesive overflows from the edge of the bonding area; Step 8. Static curing of the bonded integral part is performed under the environmental conditions of a temperature of 23°C ± 2°C and a relative humidity of 50% ± 5%. After curing for a certain period of time, the residual glue is cleaned or the workpiece is moved, and the curing is continued for a certain period of time, and the workpiece is processed or transferred to the next process; when the bonded integral part is statically cured under the environmental conditions of a temperature not lower than 15°C and a relative humidity of 15% to 75%, a tensile shear strength test is performed using a plexiglass tensile shear furnace sample. When the tensile shear strength of the sample is not lower than τ1, the residual glue of the bonded integral part is cleaned or the workpiece is moved. Then, when the tensile shear strength of the sample is not lower than τ2, the bonded integral part is processed or transferred to the next process; wherein τ1 is 2.5MPa and τ2 is 3.5MPa; Step 9. Detect the bonding surface of the first object, measure the defect size, count the defect area, and determine whether the bonding requirements are met.
2. The method according to claim 1, characterized in that In step 2, the sandpaper used to polish the bonding area of the organic glass has a specification of 300-1000 mesh, and the sandpaper used to polish the bonding area of the composite material has a specification of 100-1000 mesh.
3. The method according to claim 1, characterized in that In step 3, the air-drying time is 10 to 20 minutes.
4. The method according to claim 1, characterized in that: In step 5, the air-drying time is 10 min to 300 min.
5. The method according to claim 1, characterized in that In step 8, after curing for 24 hours under the environmental conditions of temperature 23°C ± 2°C and relative humidity 50% ± 5%, the remaining glue is cleaned or the workpiece is moved. After continuing to cure for 72 hours, processing or transfer to the next process is carried out.
6. The method according to claim 1, characterized in that In step 9, the bonding requirement is that the size of a single bonding defect shall not exceed 60mm 2 , the total defect area does not exceed 5% of the total bonding area.
7. A tensile shear strength test specimen, characterized in that: The invention comprises a first sample and a second sample, wherein the first sample is organic glass, and the second sample is a composite material or organic glass. The two samples are both rectangular sheets as the shape, and are connected by a polyurethane adhesive coated on the rectangular overlapping area, and the polyurethane adhesive is formed on the overlapping area by the bonding method of the polyurethane adhesive for organic glass as described in any one of claims 1 to 6; The back of the overlapped surface of each specimen is bonded with a steel plate bottom plate of the same size as the specimen by means of structural adhesive, and a compensation pad is bonded to the clamping end of each specimen by means of the same structural adhesive, and one end of the compensation pad is directly clamped in the chuck of the universal material testing machine; The first specimen and the second specimen have the same length and width. The thickness of specimen 1 is T1, the thickness of the second specimen is T2, the thickness of the steel sheet bottom plate on one side of the first specimen is e1, and the thickness of the compensation pad is f1, the thickness of the steel sheet bottom plate on one side of the second specimen is e2, and the thickness of the compensation pad is f2, the thickness of the structural adhesive between the specimen and the steel sheet bottom plate, and the thickness of the structural adhesive between the specimen and the compensation pad is t, and the thickness of the polyurethane adhesive layer for organic glass at the overlap of the first specimen and the second specimen is T; The thickness of the rectangular thin sheet in the overlapping area on the first sample is T1+e1+t, the thickness of the rectangular thin sheet in the overlapping area on the second sample is T2+e2+t, and T1+e1+t=T2+e2+t, f1=T2+e2+T, f2=T1+e1+T.
8. The tensile shear strength test specimen according to claim 7, characterized in that: The organic glass is biaxially stretched organic glass, cast organic glass or injection molded organic glass, and the composite material is an epoxy resin-based carbon fiber composite material.
9. The tensile shear strength test specimen according to claim 7, characterized in that: The polyurethane adhesive for organic glass is a single-component polyurethane adhesive; the structural adhesive is a two-component polyurethane adhesive, an acrylate adhesive or an epoxy resin-based adhesive, and the tensile elastic modulus is similar to the tensile elastic modulus of the sample.
10. The tensile shear strength test specimen according to claim 7, characterized in that: The curing conditions of the structural adhesive are curing at room temperature for seven days, or heating curing at 60° C. for eight hours.